The effects of addressing gender norms and access to resources on gender equality in climate-affected agrifood systems in Bangladesh - Lecoutere, Els; Akhter, Sadika; Kihoro, Esther; Kamruzzaman, Mohammed; Dey, Durjoy (CGIAR GENDER Impact Platform, 2023)
In the face of transforming agri-food systems (AFS) and climate change, it is critical to uncover potential pathways through which gender equality and resilience of AFS can be simultaneously addressed. In this quasi-experimental impact study, we assess the effects of two interventions in Kishoreganj district in Bangladesh—a climate hotspot—on women’s empowerment, intrahousehold gender equality of climate resilient capacities and AFS outcomes. One intervention addressed attitudes towards genderbased violence and gender norms (ECATTO); the other, access to resources and (extension) services for AFS activities (SHOUHARDO III). We use primary gender-disaggregated intrahousehold data collected in March 2023 from 412 households for the ECATTO and 1395 households for the SHOUHARDO III intervention (equal treatment and control proportions). We adopt matching and regression discontinuity as identification methods. We found that the ECATTO intervention increased awareness of women’s rights and more positive attitudes towards women’s political leadership among men and women. It also enhanced women’s confidence in assuming societal leadership roles. As a result of SHOUHARDO III, women are more likely to adopt farming and livestock-rearing technologies and there are smaller intrahousehold differences in technology-adoption intensity. Within the SHOUHARDO III treatment group, the couple-sessions intervention that addresses intrahousehold resource allocation has an additional positive effect on gender equality in adoption. Both the ECATTO and SHOUHARDO III interventions have a positive effect on women’s dietary diversity.